1985
DOI: 10.1111/j.1432-1033.1985.tb08891.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation by high-performance liquid chromatography of the low-molecular-mass high-mobility-group (HMG) chromosomal proteins present in proliferating rat cells and an investigation of the HMG proteins present in virus transformed cells

Abstract: The low-molecular-mass high-mobility-group (HMG) proteins from young rat thymus nuclei were fractionated by high-performance liquid chromatography. Two proteins analogous to calf HMG14 and HMGl7 were found together with a third major component HMGI similar to that found in HeLa cells [Lund et al. (1983) FEBS Lelt. 152, 363-1671. HMGI has as amino acid composition similar to but distinct from HMG14 and HMG17. The three proteins form a family of proteins with HMG14 having an amino acid composition intermediate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…An increased HMGA1 gene expression has been considered as a general diagnostic marker for neoplastic transformation (Goodwin et al, 1985;Giancotti et al, 1987Giancotti et al, , 1989 and the metastatic potential of malignant neoplasms (Bussemakers et al, 1991;Tamimi et al, 1993;Chiappetta et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…An increased HMGA1 gene expression has been considered as a general diagnostic marker for neoplastic transformation (Goodwin et al, 1985;Giancotti et al, 1987Giancotti et al, , 1989 and the metastatic potential of malignant neoplasms (Bussemakers et al, 1991;Tamimi et al, 1993;Chiappetta et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…HMG-I(Y) expression is also elevated in human uterine leiomyomata and pulmonary chondroid hamartomas, benign neoplasms (Williams et al, 1997;Xiao et al, 1997). HMG-I(Y) levels are high in neoplastic compared to normal cell lines (Goodwin et al, 1985;Giancotti et al, 1985Giancotti et al, , 1987. Increasing levels of HMG-I(Y) are found with progression in a series of cell lines isolated from the Dunning rat model system of prostate cancer (Bussemakers et al, 1991), as well as from a mouse mammary epithelial cell system (Ram et al, 1993), where increasing levels of both HMG-I(Y) mRNAs and proteins correlated with increasing metastatic potential of the tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Goodwin et al [5] have found that HMG I is present at elevated levels in proliferating rat cells compared to nondividing rat cells, supporting the notion that HMG I is required for proliferation.…”
mentioning
confidence: 84%